Trends in prosthetic biomaterials in implant dentistry - Saranjit Singh Bhasin; Eram Perwez; Shabina Sachdeva; Rizwana Mallick (Wolters Kluwer Medknow Publications, 2015)
The most important criterion for the success of dental implants is the selection of a suitable implant biomaterial. To improve the biologic performance of an implant, it is necessary to select a material that does not elicit any negative biological response and at the same time maintains adequate function. It is mandatory for a dentist to have a comprehensive knowledge of various biomaterials used for dental implants. The material of choice for fabrication of the dental implant till date is titanium. With the advancements in the field of implants, zirconia seems to be propitious in the future. However, more advanced in vitro and in vivo studies are required before reaching any such conclusion. To increase the success of zirconia implants, care should be taken to reduce the incidence of mechanical failures. Such failures can be taken care of by having a thorough technical knowledge of implant designing and manufacturing defects. This article attempts to compare the advantages and disadvantages of various dental implant biomaterials. Focus is placed on the recent advances in this field with the recently introduced zirconia and its comparison to conventional titanium.